Tinjauan Hukum Ekonomi Islam tentang Penyelesaian Perjanjian Pembiayaan Bermasalah pada Lembaga Keuangan Syariah - Dede Rohayati (PT. PENERBIT TIGA MUTIARA, 2026)
This study examines the resolution of non-performing financing in Islamic financial institutions, which have experienced significant growth but are confronted with increasing risks of non-performing financing (NPF) that may undermine institutional stability and public trust. The research problem focuses on the suboptimal mechanisms for resolving problematic financing, the existence of a gap between legal norms and their practical implementation, and the lack of integration of philosophical approaches within the framework of Islamic economic law. This study aims to analyze resolution mechanisms from the perspective of Islamic economic law, identify the factors contributing to the normative–practical gap, and formulate a more comprehensive and equitable resolution model. The method employed is normative juridical, utilizing statutory and case approaches, with secondary data analyzed qualitatively through deductive reasoning. The findings indicate that the resolution of non-performing financing is still predominantly characterized by restructuring measures that are administrative in nature and fail to address root causes, while litigation pathways remain relatively ineffective due to procedural and substantive constraints. The disparity between legal norms and practice suggests that legal implementation has not fully reflected the principles of substantive justice. The study concludes by emphasizing the necessity of reconstructing resolution mechanisms through the integration of normative, empirical, and philosophical dimensions. The novelty of this research lies in the development of a maqāṣid al-sharī‘ah-based resolution model that offers a holistic approach oriented toward justice, public welfare, and the balance of interests, thereby providing more effective, contextual, and sustainable solutions within the Islamic financial system in Indonesia.